Chemical effects of anisole and toluene addition to n‑heptane on PAH characteristics in laminar premixed flames by LIF measurement and kinetic model. (1st November 2021) - Zhang, Yiran; Jiao, Anqi; Li, Youping; Liu, Peng; Yang, Guofeng; Zhan, Reggie; Roberts, William L.; Huang, Zhen; Lin, He
Highlights: We present the LIF measurement of PAHs in n-heptane laminar premixed flames. Chemical effects of anisole and toluene addition on PAH formation were analyzed. Toluene was much more effective at promoting the PAH formation than anisole. Anisole contributes to the PAH formation via styrene and indene reaction networks. Toluene enhanced PAH formation due to the ring expansion on the dehydrogenated branch. Abstract: Anisole is a candidate renewable fuel that displays satisfying combustion characteristics, but its sooting characteristics are not well known. The goal of this study is to investigate the chemical effects of anisole and toluene on PAH formation in n-heptane laminar premixed flames, using LIF measurement and chemical kinetic simulation. To focus on chemical effects, the equivalence ratios, dilution ratios, and flame temperatures were kept nearly unchanged when anisole and toluene were blended separately into n-heptane flame. LIF experimental results indicated that PAH formation was promoted with the addition of anisole and toluene, and the effect of toluene was stronger than the promotional effect of anisole. The chemical kinetic model predicted the observed PAH tendencies well in the LIF experiments. Based on this model, reaction pathway and sensitivity analyses were performed to interpret the chemical effects. Results revealed that, due to their different molecular structures, the difference in chemical effects between anisole and toluene was notable in PAH growth processes. Anisole decomposed first via the O-CH3 bond dissociation reaction, and then proceeded to a CO elimination reaction to yield an important PAH precursor, C5 H5, which contributed to PAH formation via styrene and indene reaction networks. In the toluene added flame, PAH formation was enhanced because of ring expansion reaction on the dehydrogenated branch of the toluene.